Efektifitas Teknik Silent dalam Konseling Keluarga untuk Meningkatkan Kebersyukuran Remaja - Wiwin Sulistiyawati; Rita Silviani; Elga Yuliyanah; Imron Rosyadi; Mochamad Fariz Rizwan; Hunainah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the extent to which the silence technique in family counseling can increase gratitude among adolescents. Adolescence is a developmental period that is quite vulnerable to various emotional challenges, including low levels of gratitude caused by social pressure, family conflict, and the search for identity. The silence technique, as a counseling method, utilizes silence as a tool for self-reflection, emotional understanding, and increased individual awareness of their life experiences. Within the framework of family counseling, this approach has the potential to improve deeper communication and strengthen emotional bonds between family members. The research approach used was quantitative with a simple experimental design, which included a pre-test and post-test to assess adolescents' levels of gratitude before and after the intervention. The findings of this study showed a significant increase in adolescents' levels of gratitude after they received family counseling services using the silence technique. This indicates that the silence technique has proven effective as an intervention in increasing adolescents' awareness, acceptance, and gratitude for the lives they lead. The implications of this research are expected to serve as a reference for guidance and counseling practitioners, particularly in creating innovative, reflection-based family counseling services to improve adolescents' mental and spiritual health.